Pegmatite lithium deposits formed within low-temperature country rocks - Jinsheng Zhou; Qiang Wang; He Wang; Jinlong Ma; Guanhong Zhu; Le Zhang (Nature Communications)
Abstract The global climate crisis is likely to lead to a potential supply risk of lithium (Li) over the coming decades. More than half of the world’s production of Li is derived from Li-bearing pegmatites. Although pegmatites are widespread, only a small fraction host economically relevant Li mineralization. Revealing which factors cause some pegmatites to be enriched in Li and others to be barren is critical for understanding Li pegmatite formation and for guiding exploration for new Li resources. In this study, we used an approach involving the analysis of natural samples from the Jiajika pegmatite deposit (China), combined with thermal and diffusion modeling. Here we show that Li contents in pegmatites are controlled not only by the initial Li contents in pegmatite melts but also by the temperature of the surrounding country rocks at the time of pegmatite emplacement. Lithium-mineralized pegmatites form preferentially when Li-rich pegmatite melts intrude low-temperature country rocks.